ANÁLISE DA EVOLUÇÃO DO EMPREGO FORMAL DO MUNICIPIO DE SANTA ROSA - Lucca, Emerson J.; Pacheco, Jussiano R.; Arruda, Jônatas; Kohler, Romualdo; Trennepohl, Dilson; Schiavo, Andressa (Salão do Conhecimento, 2013)
Resumo